Allergen immunotherapy for allergic rhinoconjunctivitis: protocol for a systematic review. Issue 1 (22nd March 2016) - Dhami, Sangeeta; Nurmatov, Ulugbek; Roberts, Graham; Pfaar, Oliver; Muraro, Antonella; Ansotegui, Ignacio J.; Calderon, Moises; Cingi, Cemal; Demoly, Pascal; Durham, Stephen; van Wijk, Ronald Gerth; Halken, Susanne; et al.
Abstract: Background: The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing the EAACI Guidelines for Allergen Immunotherapy (AIT) for the Management of Allergic Rhinoconjunctivitis. We seek to critically assess the effectiveness, cost‐effectiveness and safety of AIT in the management of allergic rhinoconjunctivitis. Methods: We will undertake a systematic review, which will involve searching international biomedical databases for published, in progress and unpublished evidence. Studies will be independently screened against pre‐defined eligibility criteria and critically appraised using established instruments. Data will be descriptively and, if possible and appropriate, quantitatively synthesised. Conclusion: The findings from this review will be used to inform the development of recommendations for EAACI's Guidelines on AIT.